Development of Lumi Education Learning Media in Learning Expository Text Writing Skills for Grade X Senior High School - Jihan Fadillah; Silvia Permata Sari; Tria Putri Mustika; Mangatur Sinaga (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to develop valid and practical Lumi Education-based learning media for expository text material for grade X of Senior High School. The study was conducted at Al-Huda School, Pekanbaru, in the odd semester of the 2025/2026 academic year. This study used a research and development method with a 4D development model that includes the define, design, development, and disseminate stages. The research subjects consisted of media expert validators, language experts, material experts, and grade X students of Senior High School. Data collection techniques were carried out through validation sheets and student response questionnaires. The validation results showed that the Lumi Education learning media obtained an average percentage of 89.01% with very valid criteria. Furthermore, the results of small group trials showed an average percentage of student responses of 86.88% with a very good category, which indicates that the developed media is practical and easy to use in learning. The dissemination stage was carried out through presentation activities to Indonesian Language teachers at Al-Huda School, Pekanbaru at the SMA and SMK levels. Based on the research results, it can be concluded that Lumi Education learning media is suitable for use as an alternative digital learning media to support students’ understanding of the structure and language of expository texts.